Long-term experimental data and crop modelling to inform the ecological intensification of irrigated wheat production in South Africa. Issue 5 (20th October 2022) - Magwaza, S; van der Laan, M; Marais, D
Abstract : Wheat ( Triticum aestivum L.) production is threatened by climate change and the decline in agricultural land available due to urbanisation, farmers switching to other crops, and environmental degradation. The aim of this study was to investigate the ecological intensification (EI) of irrigated wheat production in South Africa. Data from the long-term wheat trial at the University of Pretoria and an intensive growth analysis conducted in 2019 were used to calibrate and evaluate the APSIM model. Following adequate model performance, improved management scenarios including crop rotation, manure application, optimised inorganic nitrogen (N) fertiliser application rate, objectively scheduled irrigation, and a combination of all these improved management practices together, were tested. The adoption of all management practices simultaneously was shown to be the best practice, achieving an increase of 18% in yield and reducing deep drainage and N leaching by 31%. Whereas measured data indicated a decrease in soil organic matter (SOM) from 1.20% in 1950 to 0.58% in 2019, adopting EI measures could reduce the loss of SOM to only 0.68%. Farmers are encouraged to adopt one or more of these EI management practices as their site-specific situations allow.